2022
DOI: 10.1007/s11883-022-01028-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of Dyslipidemia in Patients with Non-Alcoholic Fatty Liver Disease

Abstract: Purpose of Review Patients with non-alcoholic fatty liver disease (NAFLD), often considered as the hepatic manifestation of the metabolic syndrome, represent a population at high cardiovascular risk and frequently suffer from atherogenic dyslipidemia. This article reviews the pathogenic interrelationship between NAFLD and dyslipidemia, elucidates underlying pathophysiological mechanisms and focuses on management approaches for dyslipidemic patients with NAFLD. Recent Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 127 publications
(135 reference statements)
2
12
0
Order By: Relevance
“…[ 19 ] Dyslipidaemia is an essential mediator between NAFLD and cardiovascular disease. [ 20 ] Similar to blood pressure parameters, the delta changes in the lipid parameters between the study visits among different arms were not different. This lack of meaningful difference in blood pressure and lipid parameters could be ascribed to the young age of our study cohort and a relatively short follow-up period of 3 years.…”
Section: Discussionmentioning
confidence: 92%
“…[ 19 ] Dyslipidaemia is an essential mediator between NAFLD and cardiovascular disease. [ 20 ] Similar to blood pressure parameters, the delta changes in the lipid parameters between the study visits among different arms were not different. This lack of meaningful difference in blood pressure and lipid parameters could be ascribed to the young age of our study cohort and a relatively short follow-up period of 3 years.…”
Section: Discussionmentioning
confidence: 92%
“…Clinical studies have found that the majority of NAFLD patients suffer from dyslipidemia [ 34 ]. Similarly, levels of lipids such as FFA, TG, and TC and lipoproteins (LDL-c and HDL-c) in HFD mice serum were significantly increased compared to ND mice ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results show that TG and LDL-C are independent risk factors for NAFLD, and HDL-C is a protective factor for NAFLD. Many studies have confirmed that the excessive accumulation of lipids intensifies the production of reactive oxygen species, which destroys the steady state of redox by inducing oxidative stress and activates the inflammatory signalmediated proinflammatory reaction, thus causing further 5 Computational and Mathematical Methods in Medicine damage to the hepatocytes [32,33]. In addition, high TG can cause insulin resistance, leading to hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%